The Effect Of Audit Experience Time Budget Pressure, and Auditors’ Ethics On Audit Quality - Goodman Hutabarat (Politeknik Negeri Lampung, 2012)
The purpose of this study is to analyze the effect of audit experience, time budget pressure, and auditors’ ethics on audit quality. The research method used is survey with a sample of 85 auditors with experience in public accounting firms in Central Java. Path analysis model was used to measure the influence of exogenous variables on endogenous variables. The results showed that the audit experience, time budget pressure, and auditors’ ethics have significant influence on audit quality either simultaneously or partially. Audit experience and auditors’ ethics have a significant positive effect on audit quality. On the other hand, time budget pressure has a significant negative effect on audit quality. Keywords: audit experience, time budget pressure, auditors’ ethics, audit quality